Rural-Urban Migration and Unemployment Tendency - Mbu Daniel Tambi, Mbu Daniel Tambi; Chuo Joshua Njuh, Chuo Joshua Njuh (AFEBI Economic and Finance Review, 2020)
The study examined the effect of rural-urban migration on unemployment tendency, while controlling for other variables. We make use of the instrumental variable approach and probit controlling for endogeneity to determine the relationship between rural-urban migration and unemployment. Cameroon labour force survey is used to estimate our results. Results shows that the likelihood of unemployment decreases among rural-urban migrates compared to their rural counterparts who do not migrate. By the same token, holders of primary, secondary and tertiary levels of are less likely to be unemployed relative to their counterparts with no education, respectively. These findings have a number of policy implementations: the government could create an enabling environment for labour markets to work better for the youths seeking employment and could invest rationally on education to enable the youth become self-reliant instead of job seekers through skill development and training.